2017
DOI: 10.2147/ijn.s132304
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles induce liver fibrosis via TGF-&beta;<sub>1</sub>/Smad3 pathway in ICR mice

Abstract: The liver is one of the target organs of silica nanoparticles (SiO 2 NPs) but the toxic mechanism on the liver still remains unclear. This study aimed to explore the hepatic toxicity and its mechanism through repeated intravenous exposure to SiO 2 NPs in ICR mice. Results indicated that SiO 2 NPs could be distributed in hepatocytes, Kupffer cells, and hepatic stellate cells, and induce hepatic dysfunction as well as granuloma formation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 36 publications
4
53
0
Order By: Relevance
“…Chatteria et al investigated the mechanisms involved in amorphous silica nanoparticles mediated hepatotoxicity and suggested that the depletion of glutathione metabolism and increase of oxidative stress are among the principal causes of a silicamediated hepatotoxicity [38]. Yu et al [39] reported that intravenous injection of SiO2 NPs induced hepatic granuloma formation, oxidative damage, and apoptosis. Sadek et al [40] found that administration of SiNPs, for 15 consecutive days, caused changes in oxidative stress parameters such as malondialdehyde, glutathione reduced, catalase, superoxide dismutase, glutathione reductase, and glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Chatteria et al investigated the mechanisms involved in amorphous silica nanoparticles mediated hepatotoxicity and suggested that the depletion of glutathione metabolism and increase of oxidative stress are among the principal causes of a silicamediated hepatotoxicity [38]. Yu et al [39] reported that intravenous injection of SiO2 NPs induced hepatic granuloma formation, oxidative damage, and apoptosis. Sadek et al [40] found that administration of SiNPs, for 15 consecutive days, caused changes in oxidative stress parameters such as malondialdehyde, glutathione reduced, catalase, superoxide dismutase, glutathione reductase, and glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Mice in control groups were injected with the same volume of saline intravenously. 12 There were ten male mice in each group. Mortality and clinical manifestations of the mice were recorded.…”
Section: Methods Characterization Of Sinpsmentioning
confidence: 99%
“…9,10 Our research has demonstrated that acute exposure to SiNPs can induce liver injury via macrophage infiltration and granuloma formation, 11 whereas repeated exposure to SiNPs led to liver fibrosis in vivo. 12 However, biological effects and molecular mechanisms of SiNPs on liver are still largely unknown, especially with regard to the signal-network interaction between liver and blood.…”
Section: Introductionmentioning
confidence: 99%
“…They produce oxidative stress that in turn modulates the autophagic process in the liver, disrupting liver metabolism and homeostasis (65). This hepatic oxidative damage has been reported in both in vitro and in vivo models for AuNPs, SiO 2 NPs, and AgNPs, with differences among the NP compositions (130)(131)(132)(133)(134). However, long-term effects need to be further characterized (65).…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%